2020
DOI: 10.3389/fpsyt.2020.00799
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome in Psychosis From Mice to Men: A Systematic Review of Preclinical and Clinical Studies

Abstract: The gut microbiome is rapidly becoming the focus of interest as a possible factor involved in the pathophysiology of neuropsychiatric disorders. Recent understanding of the pathophysiology of schizophrenia emphasizes the role of systemic components, including immune/inflammatory and metabolic processes, which are influenced by and interacting with the gut microbiome. Here we systematically review the current literature on the gut microbiome in schizophrenia-spectrum disorders and in their animal models. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 166 publications
(459 reference statements)
1
25
0
Order By: Relevance
“…Fourth, CSF may not be the best biological sample for seeking cytokine abnormalities in patients with psychiatric disorders. Peripheral metabolic and microbiome alternations ( Aizawa et al, 2016 ; Rosenblat and McIntyre, 2017 ; Hidese et al, 2018 ; Horne and Foster, 2018 ; Kraeuter et al, 2020 ) may rather be more sensitive than central immunological disturbances to elucidate inflammatory changes in the pathogenesis of psychiatric disorders. Fifth, since general laboratory data about inflammatory status (e.g., CSF or plasma C-reactive protein levels) were not included, this study could not address systemic inflammation in patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, CSF may not be the best biological sample for seeking cytokine abnormalities in patients with psychiatric disorders. Peripheral metabolic and microbiome alternations ( Aizawa et al, 2016 ; Rosenblat and McIntyre, 2017 ; Hidese et al, 2018 ; Horne and Foster, 2018 ; Kraeuter et al, 2020 ) may rather be more sensitive than central immunological disturbances to elucidate inflammatory changes in the pathogenesis of psychiatric disorders. Fifth, since general laboratory data about inflammatory status (e.g., CSF or plasma C-reactive protein levels) were not included, this study could not address systemic inflammation in patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most widely used pharmacological treatments have not provided any evidence of substantial improvement and recovery in most people with chronic schizophrenia [ 23 ]. Instead, the use of antipsychotics has several side effects such as weight gain [ 45 ], diabetes mellitus [ 46 ], atherosclerosis [ 47 ], glucose metabolism dysregulation [ 48 ], and most importantly gut microbial dysbiosis [ 49 ]. The use of antibiotics and changing dietary habits are the main reasons for alteration in the gut microflora that is directly associated with modified levels of neurotransmitters and brain function [ 50 , 51 , 52 ] ( Figure 2 ).…”
Section: Antipsychotics-induced Side Effects and Gut Microbiota Dysbi...mentioning
confidence: 99%
“…The gut–brain axis and microbiome have potential roles implicated in schizophrenia pathogenesis [ 59 , 60 ]. Additionally, gut microbiome changes may contribute to schizophrenia pathophysiology and behavioral symptoms development [ 61 ]. Increasing evidence has shown that disorders such as schizophrenia are associated with gut microbiome imbalances [ 5 , 6 ].…”
Section: Gut–brain Axismentioning
confidence: 99%
“…Research on animal models has been used to discuss the possible effects of the gut microbiome on immune changes in the central nervous system and behavior, as well as their possible contributions to the pathophysiology of psychiatric disorders. Early life events may change the gut microbiome and can cause psychosis development later [ 61 ]. Early life stress can cause long term gut microbiome alterations, and may lead to neuronal malfunction and behavioral changes which have a role in psychiatric disorders.…”
Section: Stress the Gut And Schizophreniamentioning
confidence: 99%